Engaging Presence of Constructivism Philosophy in and through Management of Christian Education: Reflective Investigation - Dinata, Debi Silvia; Manuputty, Juan Andika; Hurmanisa; Tinopi, Yohana Katerina; Rudie (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This paper attempts to stitch the participation of constructivism philosophy in the space of management, education, education management, and Christian education management. Such cross-disciplinary stitching became the locus of observation as well as a response to the presence of constructivism philosophy through critical reflection in education located in Christianity. Constructivism in this paper seeks to see knowledge not as an object of transfer to learners who are often perceived as objects of education. The position of teachers, management and policy makers in access to education is located at or as facilitators. The construction of knowledge according to constructivism philosophy originates and starts from the learners themselves. Thus, the teacher's position as a faciflitator seeks to transfer and strengthen the responsibility as much as possible and according to the portion of the learner. This research is based on qualitative research with a data search model using literature studies. The literature study brings together interrelated cross-disciplines between education management and Christian education management with the philosophy of the presence of participation in the philosophy of constructivism. The results show that constructivism philosophy takes responsibility, criticizes, responds, takes part in class discussions, forms circular seating (learning strategies), and contributes innovations and sees gaps that have not surfaced in the learning process.